'A Life of Their Own'? Traditions, Power and 'As If Realism' in Political Analysis. (August 2021) - Pike, Karl
This article explores the role of tradition in the social world and offers a theory of why some traditions 'stick'. Building on the ontological insight of 'as if realism', I argue that traditions are constitutive both of an actor's beliefs and of their institutional context, and so critical to political analysis. The relative resonance of traditions can be understood as contingent upon power relations and ideational maintenance of traditions by groups of upholders – what could be termed 'socially contingent'. Traditions help us understand why a person believes what they believe and how a person's strategic calculations are affected by perceptions of what others believe. They exert a powerful pull to political actors as orientation tools in complex social settings and through the symbols and argumentation attached by those who uphold them. While traditions are contingent upon people's beliefs, it is 'as if' they have a life of their own.